Gender comparisons of exercise-induced oxidative stress: influence of antioxidant supplementation - Goldfarb, A. H.; McKenzie, M. J.; Bloomer, R. J. (Applied Physiology, Nutrition, and Metabolism, 2007)
The purpose of this study was to determine the influence of gender and antioxidant supplementation on exercise-induced oxidative stress. Twenty-five men and 23 women ran for 30 min at 80% VO2 max, once before and once after 2 weeks of supplementation, and again after a 1-week wash-out period. Subjects were randomly assigned to either placebo (P), antioxidant (A: 400 IU vitamin E + 1 g vitamin C), or a fruit and vegetable powder (FV) treatment. Blood was obtained at rest and immediately after exercise. Before supplementation, women had higher resting reduced glutathione, total glutathione, and plasma vitamin E compared with men. With both A and FV supplementations, plasma vitamin E gender differences disappeared. Protein carbonyls, oxidized glutathione, and malondialdehyde all increased similarly for both genders in response to exercise. Both A and FV attenuated the reduced glutathione decrease and the oxidized glutathione and protein carbonyls increase compared with P, with no gender differences. 8-Hydroxydeoxyguanosine was lower with treatment A compared with FV and P only for men. Plasma vitamin C increased 39% (A) and 21% (FV) compared with P. These data indicate that women have higher resting antioxidant levels than men. Markers of oxidative stress increased similarly in both genders in response to exercise of similar intensity and duration. Two weeks of antioxidant supplementation can attenuate exercise-induced oxidative stress equally in both genders.